The Rise and Fall of Chloroquine/Hydroxychloroquine as Compassionate Therapy of COVID-19 - Manivannan, Elangovan; Karthikeyan, Chandrabose; Moorthy, N. S. Hari Narayana; Chaturvedi, Subash Chandra (Frontiers in Pharmacology, 2021)
The emergence and rapid spread of novel coronavirus disease (COVID-19) has posed a serious challenge to global public health in 2020. The speed of this viral spread together with the high mortality rate has caused an unprecedented public health crisis. With no antivirals or vaccines available for the treatment of COVID-19, the medical community is presently exploring repositioning of clinically approved drugs for COVID-19. Chloroquine (CQ) and hydroxychloroquine (HCQ) have emerged as potential candidates for repositioning as anti–COVID-19 therapeutics and have received FDA authorization for compassionate use in COVID-19 patients. On March 28, 2020, the U.S. Food and Drug Administration (FDA) issued an Emergency Use Authorization (EUA) for HCQ in the treatment of COVID-19. However, it was later revoked by the FDA on June 15, 2020, after analyzing the emerging scientific data from ongoing clinical trials. Similarly, the World Health Organization (WHO) also conducted a Solidarity trial of chloroquine, hydroxychloroquine, remdesivir, lopinavir, and ritonavir. However, on May 23, 2020, the executive body of the “Solidarity trial” decided to put a temporary hold on the HCQ trial. On June 17, 2020, the WHO abruptly stopped the Solidarity trial of HCQ. The current review strives to examine the basis of compassionate use of CQ and HCQ for the treatment of COVID-19 in terms of literature evidence, establishing the antiviral efficacy of these drugs against corona and related viruses. Furthermore, the review presents a critical analysis of the clinical trial findings and also provides an insight into the dynamically changing decision on the authorization and withdrawal of HCQ as anti–COVID-19 therapy by the U.S. FDA and the WHO. Ultimately, our study necessitates an evidenced-based treatment protocol to confront the ongoing COVID-19 pandemic and not the mere observational study that mislead the public healthcare system, which paralyzes the entire world.